THE SPREAD OF PYRENOPHORA TERES ON BARLEY CROPS IN THE NORTH-CAUCASUS REGION - G. V. Volkova; I. L. Astapchuk (Зерновое хозяйство России)
The size and quality of yields are under constant threat not only because of weather conditions with its stressful effect on plants, but also pathogenic fungi, including the most harmful net leaf blotch (the causative agent Drechslera teres (Saccardo) Shoemaker (syn. Helminthosporium teres Saccardo), teleomorph: Pyrenophora teres Drechsler). In the period from 2014 to 2016, the eight regions of the North Caucasus (Labinsky, Kuschevsky, Kackazsky, Yeysky, Tselinsky GSU, Achikulaksky GSIU, Agricultural Research Center “Donskoy” and the North-Kubansky Agricultural Experimental Station named after P. P. Lukyanenko) made experiments and studied winter barley varieties infected with P. teres. Net leaf blotch was found on barley crops in all studied areas. In total there were studied 300 winter and 59 spring forms, where 117 winter and 37 spring varieties showed resistance to the disease in different years. In the southern hilly zone 15 variety samples (19% of 78 studied varieties) proved to be stable to the disease for 3 years of research. In the western pre-Azov zone 11 varieties (25% of 43 studied variety samples) showed a stable reaction. In the central part 114 barley samples were studied, where 25 variety samples (21%) showed a stable reaction to P. teres. In the east-steppe zone, 9 out of 9 (100%) variety samples were found to be stable. In the northern zone 18 samples (32%) showed a sustained resistance to the pathogen out of 56 studied ones. Thus, the largest number of resistant variety samples was found in areas located in the arid eastern steppe zone and with insufficiently stable moisture in the northern agroclimatic zone. Consequently, to protect barley from net leaf blotch pathogen, it is necessary not only to select highly resistant varieties, but also to take into account the dependence of barley infestation with P. teres on agroclimatic conditions (temperature and humidity) in different areas of the North Caucasus.